PERKEMBANGAN BAHASA PADA ANAK SEKOLAH DASAR/ MI - Riska Rudini Siregar; Wilna Wulan Suci Simatupang; Mona Hijriah Nasution; Riski Prisila; Salmida Sima Aini Siagian (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Learning in elementary schools must pay attention to aspects of student development. One aspect of development that needs to be considered is the aspect of language development. Aspects of language development will influence students' cognitive levels. Therefore, there is a need for further information regarding the language development of elementary school students. The purpose of writing this article is to provide information regarding the language development of elementary school students. This writing uses a literature study methodology by analyzing articles related to student development contained in the Google Scholar data base. Language is a communication tool used by individuals in everyday life to interact with other individuals. Language is an effective means in the process of communicating with other individuals. At the beginning of language development, it begins with the process of imitating sounds or voices without any meaning, which is then followed by pronunciation of syllables, composing simple sentences, and continuing on to more complex sentences. Elementary school age children have different developments at each age level they pass through. However, no one can ensure that aspects of students' language development have the same level of development. However, teachers as those responsible for elementary schools must ensure that student development tasks are achieved which consist of understanding, developing vocabulary, arranging words into sentences and utterances.